Modulation of Jahn–Teller distortion and electromechanical response in a Mn3+ spin crossover complex. (3rd July 2020) - Kühne, Irina A; Barker, Andrew; Zhang, Fengyuan; Stamenov, Plamen; O'Doherty, Oisín; Müller-Bunz, Helge; Stein, Matthias; Rodriguez, Brian J; Morgan, Grace G
Abstract: Structural, magnetic and electromechanical changes resulting from spin crossover between the spin quintet and spin triplet forms of a mononuclear Mn 3+ complex embedded in six lattices with different charge balancing counterions are reported. Isostructural ClO4 − and BF4 − salts (1 ) and (2 ) each have two unique Mn 3+ sites which follow different thermal evolution pathways resulting in a crossover from the spin quintet form at room temperature to a 1:1 spin triplet:quintet ratio below 150 K. The PF6 − (3 ) and NO3 − (4 ) salts which each have one unique Mn 3+ site show a complete conversion from spin quintet to spin triplet over the same temperature range. A complete two step spin crossover is observed in the CF3 SO3 − lattice (5 ) with a 1:1 ratio of spin quintet and spin triplet forms at intermediate temperature, while the BPh4 − lattice (6 ) stabilizes the spin triplet form over most of the temperature range with gradual and incomplete spin state switching above 250 K. An electromechanical piezoresponse was detected in NO3 − complex 4 despite crystallization in a centrosymmetric space group. The role of deformations associated with stress-induced spin triplet-spin quintet switching in breaking the local symmetry are discussed and computational analysis is used to estimate the energy gap between the two spin states.